2020
DOI: 10.3390/jcm9010184
|View full text |Cite
|
Sign up to set email alerts
|

The Immunomodulary Effects of Systematic Exercise in Older Adults and People with Parkinson’s Disease

Abstract: We sought to investigate whether regular balance training of moderate intensity (BT) has an effect on changes in selected cytokines, neurotrophic factors, CD200 and fractalkine in healthy older adults and participants with Parkinson’s disease (PD). Sixty-two subjects were divided into groups depending on experimental intervention: (1) group of people with PD participating in BT (PDBT), (2) group of healthy older people participating in BT (HBT), (3,4) control groups including healthy individuals (HNT) and peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 56 publications
6
39
0
Order By: Relevance
“…A recent randomized controlled trial investigated the effects of a specific training program to modulate systemic inflammation (38). After this intervention, serum levels of TNF-α, IL-6, and IL-10 were significantly lower in the intervention group, confirming the anti-inflammatory properties of physical exercise previously demonstrated in several pathological conditions (39)(40)(41)(42) and suggesting a possible mechanism through which it intervenes in countering BCF clinical manifestations. Of note, given the lack of adverse events in our study group, we confirm the excellent safety profile of this physical exercise intervention.…”
Section: Discussionsupporting
confidence: 52%
“…A recent randomized controlled trial investigated the effects of a specific training program to modulate systemic inflammation (38). After this intervention, serum levels of TNF-α, IL-6, and IL-10 were significantly lower in the intervention group, confirming the anti-inflammatory properties of physical exercise previously demonstrated in several pathological conditions (39)(40)(41)(42) and suggesting a possible mechanism through which it intervenes in countering BCF clinical manifestations. Of note, given the lack of adverse events in our study group, we confirm the excellent safety profile of this physical exercise intervention.…”
Section: Discussionsupporting
confidence: 52%
“…Szymura et al. ( 2020 ) have previously demonstrated that similar balance training induces neuroprotective mechanisms in both HOA and individuals with PD. The lack of differences between HOA and individuals with PD in our study extends these findings and suggests that disease‐inclusive exercise training may be equally effective for both groups and thus may maintain physical and cognitive functions in older adults with or without PD.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to TGF-β1, the plasma concentration of this neurotrophin increases in response to exercise (1 h of treadmill running) (Heinemeier et al, 2003). In a different study enrolling healthy people and Parkinson subjects, the immunomodulatory effects of moderate intensity on plasma neurotrophins levels was investigated (Szymura et al, 2020). Szymura et al (2020) demonstrated that after completion of the 12 weeks training program the concentration of TGF-β1 as well as of other neurothophic factors (nerve growth factor and BDNF) were found to be increased only in training groups.…”
Section: The Pathophysiology Of Depression: the Role Of Neurotrophic mentioning
confidence: 99%
“…In a different study enrolling healthy people and Parkinson subjects, the immunomodulatory effects of moderate intensity on plasma neurotrophins levels was investigated (Szymura et al, 2020). Szymura et al (2020) demonstrated that after completion of the 12 weeks training program the concentration of TGF-β1 as well as of other neurothophic factors (nerve growth factor and BDNF) were found to be increased only in training groups. Furthermore, in a study considering a total of 29 athletes, the serum levels of TGF-β1 were higher in athletes with high relative Vo 2 peak (relVo 2 peak) values, a measure of the athletes' cardiovascular fitness and aerobic endurance, compared to low relVo 2 peak (Weinhold et al, 2016).…”
Section: The Pathophysiology Of Depression: the Role Of Neurotrophic mentioning
confidence: 99%